Global trends in the prevalence of secondhand smoke exposure among adolescents aged 12–16 years from 1999 to 2018: an analysis of repeated cross-sectional surveys. Issue 12 (December 2021) - Ma, Chuanwei; Heiland, Emerald G; Li, Zilin; Zhao, Min; Liang, Yajun; Xi, Bo
Summary: Background: Secondhand smoke exposure can cause morbidity and premature mortality. However, the global prevalence of, and trends in, secondhand smoke exposure among adolescents are poorly documented. We aimed to assess the prevalence of, and trends in, secondhand smoke exposure among adolescents from 1999 to 2018. Methods: We did an analysis of the most recent data from the Global Youth Tobacco Survey (GYTS), a nationally representative, self-administered, school-based cross-sectional survey of tobacco use and related factors among adolescents aged 12–16 years worldwide. Data from 142 countries and territories that had done a GYTS between 2010 and 2018, comprising 711 366 participants, were used to assess the prevalence of secondhand smoke exposure. Data from 131 countries and territories that had done two or more surveys between 1999 and 2018, comprising 1 405 458 participants, were used to assess trends in secondhand smoke exposure. The frequency of secondhand smoke exposure at home, in public places, or in any place was defined as follows, based on students' responses: 1 or more days, 3 or more days, 5 or more days, or daily during the past 7 days. Findings: Based on the most recent surveys done in 142 countries between Jan 1, 2010, and Dec 31, 2018, the global prevalence of secondhand smoke exposure in any place was 62·9% (95% CI 61·7–64·1) on 1 or more days, 51·0% (49·8–52·1) on 3 or more days, 40·1% (38·9–41·2) on 5 or more days, and 32·5% (31·5–33·6) daily during the past 7 days. The prevalence of secondhand smoke exposure at home was 33·1% (95% CI 32·1–34·1) on 1 or more days, 20·1% (19·3–20·9) on 3 or more days, 14·9% (14·2–15·7) on 5 or more days, and 12·3% (11·7–13·0) daily during the past 7 days; and in public places the prevalence of secondhand smoke exposure was 57·6% (56·4–58·8) on 1 or more days, 43·4% (42·2–44·6) on 3 or more days, 30·3% (29·2–31·5) on 5 or more days, and 23·5% (22·5–24·5) daily during the past 7 days. Between Jan 1, 1999, and Dec 31, 2018, the prevalence of secondhand smoke exposure (on ≥1 day during the past 7 days) in any place decreased in 57 (43·5%) of 131 countries, increased in 27 (20·6%), and remained unchanged in 47 (35·9%). Although the prevalence of secondhand smoke exposure at home decreased in 86 (65·6%) countries, the prevalence in public places did not change in 46 (35·1%) countries and increased in 40 (30·5%). Interpretation: Secondhand smoke exposure among adolescents remains a serious public health challenge worldwide. Although the prevalence of secondhand smoke exposure at home decreased in most countries, the prevalence in public places increased or remained unchanged in most countries between 1999 and 2018. These findings emphasise the need to strengthen smoke-free policies, especially in public places. Funding: Youth Team of Humanistic and Social Science of Shandong University, Jinan, China. Translation: For the Chinese translation of the abstract see Supplementary Materials section.